A Financial Model of Foreign Exchange Exposure - Hekman, Christine R. (Journal of International Business Studies, 1985)
The paper describes a model of foreign exchange exposure. This is defined as the sensitivity of a specific investment's value in reference currency to changes in exchange rate forecasts. This sensitivity may result because some share of the investment cash flows are denominated in foreign currency. Alternatively, a share of cash flows denominated in reference currency which are affected by future exchange rates can also generate sensitivity.